Plant Food Allergens. - Mills, Shewry (John Wiley & Sons, 2007)
This volume provides a thorough scientific account of contemporary knowledge of the occurrence, properties and characteristics of plant food allergens. It also thoroughly discusses their properties in relation to dietary exposure, food processing and GM foods.